Development of implementation strategies for using a web-based app for screening in men in the primary care setting - Ooi, Chor Yau; Ng, Chirk Jenn; Sales, Anne E.; Ong, Yee Ching (2020)
Background: Web-based apps have been used to address different health needs including health screening, health promotion, and health advice. Studies have shown that web-based apps are effective in changing health behaviors and improving health status. However, not much is known about implementation of such apps. This study aimed to develop implementation strategies for using a novel web-based app to screen men in the primary care setting. Methods: In the first phase of the study, a qualitative study was conducted to explore determinants for implementation. Participants were health care providers and patients from three government health clinics in Kuala Lumpur, the capital city of Malaysia, in 2019. Semi-structured in-depth interviews and focus group discussions were conducted guided by the Tailored Implementation in Chronic Disease (TICD) framework. The interviews were audio recorded and transcribed verbatim. Data were analyzed using directed content analysis with a deductive approach. The determinants were determined using a rating system recommended by Damschroder and Lowery. The ratings reflected the valence (positive or negative influence) and the magnitude or strength of each determinants. In the second phase, implementation strategies were developed using explorative methods. A brainstorming session was conducted with experts in primary care and implementation science as well as the web-app developer to develop implementation strategies. Implementation strategies developed were classified using The Expert Recommendations for Implementing Change (ERIC) classification. Subsequently, the implementation strategies were refined and evaluated with the APEASE (Affordability, Practicability, Effectiveness and cost-effectiveness, Acceptability, Side-effects/safety, Equity) criteria to determine the optimal implementation strategies. Findings: From the qualitative study, 11 barriers and 12 facilitators were identified based on the TICD framework. One barrier, language, was not part of the TICD framework. The implementation strategies developed were: provide education, involve executive boards, remind clinician, mandate change, create new clinical teams, identify and prepare champions, develop and organize quality monitoring systems and alter incentive/allowance structures. Implications for D&I Research: This study detailed the process of developing the implementation strategies for a novel web-based app. Because not many studies focused on development of implementation strategies for web-based apps, this study can be a guide for future studies in this area.